渺小的伟大 ：以电视剧《大英雄》探讨新加坡小市民的邻里关系 = Building Singapore's neighbourhood relations : a case study of drama series Hero - 林殷如 Lim, Esther Yin Ru (2018)
“政府组屋”是新加坡独特的人文风景。邻里关系可视为这一座座政府组屋所散发的生活气场。在促进邻里关系上，新加坡政府不遗余力。但解铃还须系铃人，无论政府如何帮忙，居民对促进邻里关系的贡献是至关重要的。居民的自主性并非政府所能直接植入。政府唯独能做的是鼓励居民自动自发促进邻里关系，以填补政府在协助促进邻里关系的职能中所留下的空缺。《大英雄》是一部以邻里关系为背景的新加坡华语电视剧。剧中小人物守望相助的甘榜之情动人。本研究发现新加坡华语电视剧能有效地反映政府话语，发挥社会作用。新加坡华语电视剧或许是政府寻求鼓励人民发挥自主精神的一个途径。虽然电视剧为了戏剧张力而夸大了邻里互动与互助事件，但《大英雄》的合理性高，多方面扣合现实，是个突出的社会文本。观众对剧中英雄人物有所向往。虽然观众或许不会因一部剧而采取行动促进自己的邻里关系，但他们能了解并认同剧中所再现的邻里关系是美好的，也是他们所向往的一种邻里关系。The existence and abundance of Public Housing Flats in the nation's skyline is a landscape unique to Singapore. Despite The Singaporean Government’s relentless efforts in promoting healthy and robust neighbourly relations, it is equally paramount that residents are active and keen on contributing to these aforementioned relations. There are limitations as to how the government can instill a sense of initiative in citizens to be proactive in the building of these relations. The government make an attempt to encourage and foster a sense of spontaneity in Singaporeans to actively seek out the betterment of relationships between one and one’s neighbours, in hope that this would make up for the lack in its role. Hero is a local Chinese Language drama based on neighborly relations. The display of the “kampong spirit” in the show is particularly moving, in that the neighbors exhibited a strong sense of initiative and camaraderie, proactively and generously seeking to help each other in times of need. Research shows that Singapore Chinese Language TV drama is effective in reflecting Government discourse, hence playing an important social role and is probably a channel for government to arouse residents’ willingness. Hero is extremely realistic despite it's theatrical exaggerations, making it a good reflection of the reality in Singapore's social context. Audiences yearn for heroic TV characters in their own neighbourhood. It is reflected that after watching just one drama of this genre, viewers may not take action to improve their neighbourly relations. Nonetheless, they were able to understand and identify themselves with the beautiful neighbourly relations portrayed in the drama and this is something that they longed for.